Collection and management of Ziswaf for the prosperity of the ummah - Ahmad Muqorobin (Journal of Islamic Economics Management and Business (JIEMB), 2022)
One of Ziswaf’s goals in Islam is to contribute to creating people’s welfare and alleviating poverty. This study examines the strategy for collecting and managing Ziswaf funds at the BaitulQur’an Social Fund Institution (LDSBQ), which has a vision and mission based on Islamic sharia and aims to prosper the ummah.The research uses a qualitative approach with descriptive analysis methods, while instruments in data collection use interviews, observation, and documentation. Sources are taken from various references related to the problem topic, namely journals, books, and other articles. The result of this study shows the three main programs of LDSBQ. First, Scholar Smileengaged in education. Second, Healthy Smileoperates in the health sector. Third, Independent Smile is a movement for community independence in the economic field, supported by socio-religious activities such as waqf and da’wah programs. This research has implications for the fundraising strategy of Gontor.Meanwhile, the fundraising strategy uses a potential network of guardians of students and teachers, a network of Gontor alumni colleagues with a movement based on the real sector, and community social activities that can have a significant impact on the welfare of the ummah to get happiness in the world and the hereafter.Keywords: Ziswaf; social institution; collection; management; welfare of the ummah.